227k views
2 votes
Solve 2^(x-1) =11 change of base

User Cup
by
4.6k points

2 Answers

1 vote

Answer:

x = 4.46

Explanation:

We are to solve the following expression:


2^((x-1))=11

Taking the natural logarithm of both sides of the equation to remove the variable from the exponent. to get:


ln ( 2 ^ { x - 1 } ) = l n ( 1 1 )


( x - 1 ) l n ( 2 ) = l n ( 1 1 )

Applying the distributive property:


xln(2)-1ln(2)=ln(11)

Solving for x to get:


x=(ln(11))/(ln(2)) +1

x = 4.46

User Extrapolator
by
5.1k points
1 vote

Answer:


x=4.459

Explanation:

We have the following equation


2^((x-1)) =11

To solve the function, apply the equation
log_2 on both sides of the equation


log_2(2^((x-1))) =log_2(11)

Remember that


log_b(b)^x =x

So


(x-1) =log_2(11)


x =log_2(11) + 1

Finally


x=4.459

User Ristapk
by
4.9k points